DISTRIBUTION OF BIRDS IN SOME OASES IN THE NORTHERN PART OF THE SAHARA - GUEZOUL, O.; ABABSA, L.; SOUTTOU, K.; SEKOUR, M. (Courrier du Savoir, 2017)
In some oases of the northern part of the Sahara, those of the basin of Ouargla, Biskra and that of Oued Souf, the birds are studied. In the palm groves of the Ouargla basin 43 species belonging to 4 orders, 13 families and 21 genera are listed. Further north, in a Ziban (Biskra) palm grove, 49species are mentioned, representing 11% of the total Algerian species which correspond to 21 families of which the best represented are Turdidae, Columbidae and Sylviidae. In Oued Souf, 32 species are inventoried belonging to 17 families, in particular the Sylviidae. In Ghardaïa, among the 38 species, the Turdidae ranked first with 8 species (21.1%). Within these species, three appear to have settled as Streptopelia decaocto, even in a state of expansion, such as Passer domesticus x P. hispaniolensis.